Genre, guerre et militarisme à travers le prisme de l’art féministe : un cheminement intime. - Adela Jusic; Nermina Trbonja (Genre, Sexualité et Société)
The interview with Adela Jusic opens the debate on the role of the artist in the creation of visual representations in the context of post-war Bosnia and Herzegovina. Following her career pathway, Adela Jusic explains how her feminist engagement is embodied in her artistic practice. Through visual art, her work aims to break stereotypes, deconstruct patterns, denounce injustices and engender changes. Through multiple examples of her work, she offers an unprecedented reading of her feminist commitment and discusses militarization, the place of the victims in the contemporary post-war space, the gendered violence perpetrated through rape, and the issue of remembrance blurring the history of Bosnia and her family history.